Understanding the Push and Pull Motivational Factors Of Technology Usage for Traveling among Women Students in USM, Penang - Ratthinan, Senutha P.; Selamat, Nor Hafizah (Global Academic Excellence, 2017)
Students - young, gutsy and tech savvy are becoming an important segment of the travel industry. A report by UNWTO and WYSE shows that the global youth and student travel industry will reach 300 million international youth trips per year. The data also underlines the increasingly important role of women travellers in student travel segment. Their technology proficiency enables them to fulfil a seamless travel experiences besides maintaining a ‘symbolic proximity’ with family and friends while establishing a sense of ‘presence while absent’. This paper seeks to understand the underlying motivations of women students at Universiti Sains Malaysia, Penang to use technology for traveling. Using in depth interviews from 10 women student travelers aged between 20-35 years old, the aspects of their backgrounds and motivations were analysed. The findings indicate three distinct push and pull factors that impacts their motivation. The finding reinforces the increasing demand for travel among women students and the fact that technology has fundamentally reshaped the way travel is planned. This call for tourism stakeholders to make significant shift towards innovative initiatives that will be able to enhance the potential of the youth and student niche market.